Kincaid, Anderson County - Starkey, Emily (Kansas State University, The Chapman Center for Rural Studies, 2017)
Kincaid, in Rich Township, Anderson County, Kansas had less than 200 people as of the 2010 U.S. Census. Once a year this number does a 100-fold increase because of the town’s annual “World’s Fair.”
Emily Starkey, “Kincaid, Anderson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/204.
Keywords: Anderson; Anderson County; fair; Kincaid; Rich Township; St. Louis and Emporia Railroad